GELIAT MODERNISASI DAN UPAYA PREVENTIF ORANGTUA DALAM MENINGKATKAN KUALITAS KEPRIBADIAN ANAK (Studi di Kecamatan Mandongan Kota Kendari) - Supiyah, Ratna (SOCIETAL, 2014)
This research aims at describing and analyzing the effort done by the parents in increasing the quality of children’s personality in the effect of modernization. This research was conducted in Mandonga District, Kendari Town, with the consideration that this location denotes one of the areas which has the most complex and heterogeneous citizens. The unit of analysis in this research was the parents who have adult children in which the information was obtained through observational technique, in-deep interview, and written document research. Furthermore, the data were analyzed in qualitative descriptive, in which the processing and analysis of data were done simultaneously. The findings elaborated that the form of parents’ preventive effort in advancing the quality of children’s personality, consisted of: fulfilling children’ rights, educating the children with love, instilling religious value since early, and keeping the children away from the negative effects. Therefore, it is expected for the parents in order to have broad insight and adequate religious knowledge base to avoid the mistakes in educating their children. Key Words: Modernization, Parents, Children’s personality.